Consequentiality and Opt-out Responses in Stated Preference Surveys. (December 2014) - Hwang, Joonghyun; Petrolia, Daniel R.; Interis, Matthew G.
Abstract : The objective of this study was to test for the effect of consequentiality on the probability of a respondent opting out of voting in a stated preference survey. We find that respondents who believe that the survey is inconsequential are more likely to opt out than to vote yes in both binomial-choice and multinomial-choice formats and are more likely to vote no than to opt out in the multinomial-choice format. We also find that respondents who are uncertain about consequentiality are more likely to opt out than to choose yes or no under both choice formats.